Citrullination as early-stage indicator of cell response to single-walled carbon nanotubes. - PRINA MELLO, ADRIELE (My University, 2013)
Single-walled carbon nanotubes (SWCNTs) have been widely explored as potential technologies for information systems and medical applications. The impact of SWCNTs on human health is of prime concern, if SWCNTs have a future in the manufacturing industry. This study proposes a novel, inflammation-independent paradigm of toxicity for SWCNTs, identifying the protein citrullination process as early-stage indicator of inflammatory responses of macrophages (THP-1) and of subtle phenotypic damages of lung epithelial (A549) cells following exposure to chemically-treated SWCNTs. Our results showed that, while most of the cellular responses of A549 cells exposed to SWCNTs are different to those of similarly treated THP-1 cells, the protein citrullination process is triggered in a dose- and time-dependent manner in both cell lines, with thresholds comparable between inflammatory (THP-1) and non-inflammatory (A549) cell types. The cellular mechanism proposed herein could have a high impact in predicting the current risk associated with environmental exposure to SWCNTs
PUBLISHED
Keywords: Single-walled carbon nanotubes; Single-walled carbon nanotubes; Immunology, Inflammation & Infection; Nanoscience & Materials